Impact of Climate and Land Use Changes on the Livelihood of Residents in Calabar River Basin, South-eastern Nigeria - Tariah, Ibiso Michael Inko; Abali, Temple Probyne; Aminigbo, Leonard Michael Onyinyechi (Journal of Sustainability and Environmental Management, 2022)
Human activities such as deforestation, urbanization, and fuel combustion have caused climatic and land use changes, affecting the livelihood of residents negatively in Calabar River Basin, South-eastern Nigeria. In the region, there has been a constant and prolonged rise in temperature. To determine the status of climatic change, data sets spanning 43 years (1971-2014) were obtained from the Nigerian Meteorological Agency (NIMET) and compared to NIMET’s historical meteorological data maps of Nigeria between 1941-1970 and 1971-2000, commonly known as the base period. In contrast, utilizing imageries from several satellites (Landsat), multi-temporal dates (MSS 1980, TM 1990, ETM 2000, and ETM+2010) and ArcGIS, researchers were able to determine the Land Use Changes / Land Covers (LULC) that have occurred in the Calabar river basin through time (1980-2020). Climate data revealed a historical sequence of temperature rises, as evidenced by late beginning and early cessation of rainfall, which had a negative influence on agriculture. Similarly, the investigation found that the environment has been warmer as temperatures have risen significantly, and that the harmattan dust haze has also increased in recent years. The investigation for LULC came up with six broad classifications: urban (built-up), water bodies, forest, farm, grass, and bare areas. Built-up area and farmland land uses have increased dramatically (3.19%-20.73%) and (10.20% -23.79%), respectively; forest (35.85%- 24.84%), water bodies (8.77%- 5.27%), Grassland (24.68%- 12.67%), and bare land uses have decreased dramatically (17.31%-12.69%). Since 1941 through 2020, temperatures have risen at a pace of 0.14° F (0.08° C) every decade, and the rate of warming is more than twice that: 0.32° F (0.18° C) per decade. The shortening of the rainy season has been forced by the late start and early cessation of rains. This has had a negative impact on the region’s farming activities. The study recommends reforestation and the formation of forest reserves, greater energy efficiency, a shift to renewable resources / cleaner sources of energy (solar and wind), and reduced deforestation to mitigate the risks connected with climate and land use changes.